2008
DOI: 10.36076/ppj.2008/11/343
|View full text |Cite
|
Sign up to set email alerts
|

Increased Knee Cartilage Volume in Degenerative Joint Disease using Percutaneously Implanted, Autologous Mesenchymal Stem Cells

Abstract: Background: The ability to repair tissue via percutaneous means may allow interventional pain physicians to manage a wide variety of diseases including peripheral joint injuries and osteoarthritis. This review will highlight the developments in cellular medicine that may soon permit interventional pain management physicians to treat a much wider variety of clinical conditions and highlight an interventional case study using these technologies Objective: To determine if isolated and expanded human autologous me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…32 In general, OA is considered to be a systemic disease and decreasing overall inflammation represents one mechanism by which MSCs can assist in supporting cartilage health. 33 Although movement of guinea pigs on the treadmill improved with treatment, we did not detect a histological change in the joint at the end of the study, which is consistent with other studies of similar duration. 34 Given the short timeframe following injection, we did not anticipate structural improvements.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…32 In general, OA is considered to be a systemic disease and decreasing overall inflammation represents one mechanism by which MSCs can assist in supporting cartilage health. 33 Although movement of guinea pigs on the treadmill improved with treatment, we did not detect a histological change in the joint at the end of the study, which is consistent with other studies of similar duration. 34 Given the short timeframe following injection, we did not anticipate structural improvements.…”
Section: Discussionsupporting
confidence: 91%
“…Further, modulation of the PGE 2 pathway has been demonstrated to ameliorate inflammation in OA 32 . In general, OA is considered to be a systemic disease and decreasing overall inflammation represents one mechanism by which MSCs can assist in supporting cartilage health 33 …”
Section: Discussionmentioning
confidence: 99%
“…Injecting human umbilical cord MSCs into the joint cavity to treat degenerative knee arthritis has been shown in clinical trials to significantly enhance patient quality of life and joint function [27]. A severe case of knee OA was described by Centeno et al After six months of injection of bone marrow, MSCs grown in phosphate buffer suspension, the ROM score rose and the VAS pain score fell [28]. At a 6-month follow-up, the European Union reported a phase I trial on a preliminary series of 18 patients and found that MSCs produced from fat decreased the pain and function component scale of WOMAC [29].…”
Section: Clinical Stem Cell Studiesmentioning
confidence: 99%
“…In recent years, stem cell therapies, especially the transplantation of MSCs, have been widely used in the field of regenerative medicine. In spite of achieving some remarkable results in ACD and early OA treatment (Murphy et al, 2003;Centeno et al, 2008;Jo et al, 2017) many safety risks limit its wide application in clinical practice, such as immune rejection (Zhang et al, 2013) and tumorigenic potential of transplanted cells (Nori et al, 2015). With the deepening of research, an increased amount of evidence showed that the beneficial effects of stem cell transplantation might not be limited to its multi-differentiation potential but more related to the paracrine secretion of trophic factors, among which EVs are considered to be one of the most critical functional components (Meirelles et al, 2009;Jin et al, 2011;Wu et al, 2011).…”
Section: Role Of Evs In the Treatment Of Articular Cartilage Lesions And Degenerative Joint Diseasesmentioning
confidence: 99%